Assessment of Marital Adjustment and Sexuality in Women With Rheumatoid Arthritis - Rabia ÖNEM,; Selime ÇELİK,; Jülide ÖNCÜ,; Onur TANKAYA,; Uğur KOLAT,; Birim SUNGU DANIŞMANT,; Can Sait SEVİNDİK,; Ömer Akil ÖZER, (Archives of Rheumatology, 2014)
Objectives: Physical distress in patients with rheumatoid arthritis (RA) may affect marital adjustment and sexual functioning. This study aims to investigate marital adjustment and sexuality in female patients with RA. Patients and methods: The patient group consisted of 47 female patients with a diagnosis of RA between the ages of 18-55 (mean age 37.36±7.21 years), married and who have not entered menopause yet. Forty-five healthy women were included as a control group. Golombok Rust Inventory of Sexual Satisfaction (GRISS), Arizona Sexual Experiences Scale (ASEX), Dyadic Adjustment Scale, Beck Depression Scale, Beck Anxiety Scale, and Disease Activity Scores in 28 joints were evaluated. Results: The mean disease duration was 4.77±4.61 years. There was no significant difference between the groups with regard to total and sub scale scores of Dyadic Adjustment Scale and GRISS total scores (p>0.05). A significant difference was found between the groups with regard to ASEX total score (p<0.05), ASEX-objective sexual arousal (p<0.05), ASEX-subjective sexual arousal categories (p<0.01), and GRISS-anorgasmia subscale (p<0.01). A positive correlation was found only between the number of tender joints and anorgasmia subscale of GRISS (p<0.05). Conclusion: Rheumatoid arthritis does not affect marital adjustment of patients; however, may affect sexual functioning to some extent leading to a need for psychiatric care.